Systematic review of effects of current transtibial prosthetic socket designs—Part 2: Quantitative outcomes - Safari, Mohammad Reza; Meier, Margrit Regula (Journal of rehabilitation research and development, 2015)
This review is an attempt to untangle the complexity of transtibial prosthetic socket fit and perhaps find some indication of whether a particular prosthetic socket type might be best for a given situation. In addition, we identified knowledge gaps, thus providing direction for possible future research. We followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, using medical subject headings and standard key words to search for articles in relevant databases. No restrictions were made on study design and type of outcome measure used. From the obtained search results (n = 1,863), 35 articles were included. The relevant data were entered into a predefined data form that included the Downs and Black risk of bias assessment checklist. This article presents the results from the systematic review of the quantitative outcomes (n = 27 articles). Trends indicate that vacuum-assisted suction sockets improve gait symmetry, volume control, and residual limb health more than other socket designs. Hydrostatic sockets seem to create less inconsistent socket fittings, reducing a problem that greatly influences outcome measures. Knowledge gaps exist in the understanding of clinically meaningful changes in socket fit and its effect on biomechanical outcomes. Further, safe and comfortable pressure thresholds under various conditions should be determined through a systematic approach.